PENELANTARAN EKONOMI DALAM KELUARGA (TINJAUAN FIQH DAN UU PKDRT) - Khairani Khairani (Takammul : Jurnal Studi Gender dan Islam Serta Perlindungan Anak, 2017)
Nowadays, ignoring family often results separation inside the family, especially after the avail- ability of Law Domestic Violence (Domestic Violence Act). However, Islamic judiciance (Fiqh) looks differently toward this case so that it is necessary to study fiqh muqarran. Furthermore, this argument needs to be related to the phenomenon that occurs due to the Domestic Violence Act.